KONSEP ISLAMIC FINANCIAL TECHNOLOGY (FINTECH SYARIAH) DAN TRUST (KEPERCAYAAN) KONSUMEN - Masniah; Khuzaini; Syahrial Shaddiq (PT. Saha Kreasi Indonesia, 2025)
A Systematic Literature Review (SLR) was conducted to analyze the dynamic relationship between Sharia Fintech and Consumer Trust in Indonesia, synthesizing findings from eleven academic articles published between 2020 and 2025. The thematic synthesis confirms that Trust is a fundamental prerequisite for successful adoption and is driven by two main pillars: Sharia Compliance Trust (The Syariah Trust), which is fueled by transparent contracts and strong Sharia Supervisory Board (DPS) governance, and Technical/Functional Trust (The Technical Trust), which is heavily influenced by Perceived Risk (data security) and system quality. The findings indicate that Trust is a strong predictor of Adoption Intention and positively correlates with increased Financial Inclusion among MSME actors. However, the research highlights significant contradictions regarding the direct role of Literacy and Knowledge as antecedents of Trust, suggesting a need for further research. Recommendations are directed towards the necessity of qualitative research to understand the process of Trust recovery, and for platforms to invest in robust compliance governance and functional digital literacy education.